2023 IJSPT Orthopedic Summit Research Abstracts - International Journal of Sports Physical Therapy (International Journal of Sports Physical Therapy)
The International Journal of Sports Physical Therapy is pleased to publish abstracts from the thirteenth Orthopaedic Summit (OSET) taking place in Boston, September 19-23, 2023. The IJSPT hosted the third annual research forum and reception at OSET, sponsored by ATI Physical Therapy and Hyperice. The abstracts presented in the following pages were selected by the OSET Research Committee and editorial staff of the International Journal of Sports Physical Therapy. After careful review, a total of 20 research abstracts were accepted and presented at OSET 2023. Awards for outstanding abstracts were presented on September 22.